Delayed symptomatic renal arteriovenous fistula in a 24 years old male following renal biopsy - Büttner, Thomas; Ellinger, Jörg; Fechner, Guido; Hauser, Stefan; Cox, Alexander; Stein, Johannes; Krausewitz, Philipp (Urology case reports, 2024)
We report a case of a 24-year-old male with a history of kidney biopsy at young age due to chronic renal dysfunction and challenging hypertension, who presented with flank pain and hematuria. Initial imaging suggested renal pelvis enlargement, but MRI revealed a massive renal arteriovenous malformation (AVM). Angiographic embolization was abandoned due to extensive effluent flow, followed by successful surgical resection preserving healthy kidney tissue. This case underscores the importance of considering renal AVMs in the differential diagnosis of young patients with gross hematuria or refractory hypertension to prevent complications and improve patient outcomes.